Tailoring of two-dimensional electron gas density in thin film oxide heterostructure via atomic layer deposition - Kim, Seong Hwan; Kim, Hye Ju; Lee, Sang Woon (Proceedings of the World Congress on New Technologies, 2019)
Recently, oxide heterostructure-based two-dimensional electron gas (2DEG) has received intensive attentions owing to their interesting properties. The model system is epitaxial LaAlO3 (LAO) grown on single crystalline SrTiO3 (STO) substrate.[1] Electrons with a density of 1013~1014/cm2 were observed which moves freely along in-plane direction while they are confined within ~2 nm (out-of-plane direction). Unfortunately, the adjustment of electron density was not available for the epitaxial LAO/STO heterostructure. In addition, the growth of epitaxial LAO film requires a high-temperature process (700 ~ 800°C) using pulsed laser deposition technique. Here, we demonstrated a creation and control of 2DEG at the interface of non-epitaxial Al2O3/TiO2 thin film heterostructure using atomic layer deposition (ALD). The electron density can be tailored from ~ 1011/cm2 to ~ 1014/cm2 by the control of ALD process temperature because the electrons are coming from oxygen vacancies at the interface of Al2O3/TiO2 heterostructure of which oxygen vacancy density is governed by kinetics during the ALD process. Electron density up to ~1014/cm2 was achieved at the interface of the Al2O3/TiO2 heterostructure which is 100 times higher than that of the conventional semiconductor heterojunction such as AlGaAs/GaAs. The 2DEG at Al2O3/TiO2 heterostructure can be applied for the development hydrogen (H2) gas sensor. A highperformance, transparent, and extremely thin (<15 nm) hydrogen gas sensor was fabricated using 2DEG at the interface of Al2O3/TiO2 heterostructure grown by ALD. [2] Palladium nanoparticles (≈2 nm in thickness) are used on the surface of the Al2O3/TiO2 thin film heterostructure to detect H2. Both oxides with a wide bandgap (>3.2 eV) have transmittance of 83% in the visible spectrum, which allows for a transparent sensor. The Pd/Al2O3/TiO2 gas senor detects H2 gas quickly with a short response time of <30 s even at room temperature which outperforms conventional H2 gas sensors. This sensor responds to a wide range of H2 concentration, especially from ~5 ppm to 1%, implying a promising candidate for a general H2 sensor. Interestingly, the Pd/Al2O3/TiO2 gas senor showed an optimal electron density for H2 detection owing to the tailoring ability of 2DEG at the Al2O3/TiO2 heterostructure. Particularly, a sensitivity was as low as 3% for a 2DEG density of 5.6 × 1013 cm-2 while the sensitivity was improved from 6% to 43% as the electron density decreased from 5.6 × 1013 cm-2 to 4.1 × 1011 cm-2. Besides the sensor application, other application of 2DEG will be introduced in the presentation.